Leading KidMin : how to drive real change in children's ministry - Cimo, Pat (Chicago : Moody Publishers, 2016)
Want to see your church's kids transformed for Jesus? Struggling to get the whole church on board? Know what you want to see happen, but not how to make it happen? Leading KidMin is about what it takes to achieve big-time change. Moving past the "why" and getting straight to the "how," Leading Kidmin provides tools and strategies for actually leading, influencing, and implementing change on a local church level—all from the vantage point of the children's ministry director. The mission of Leading KidMin is to create a movement of change-agents who don't just know that change is needed, but are equipped to make it happen, leading their churches in becoming more aligned, effective, and geared for growth. Pat Cimo and Matt Markins, veterans of KidMin, are prepared to make you the change-agent you want to be—and that your church needs you to be. Are you ready? -from publisher.
Breaking out of the vicious trend cycle-and lead! -- Gaining clarity: for yourself, for others -- How to run toward your problems -- Aligning to a larger vision -- How to be a student of your senior pastor -- Building partnerships that work -- listening to those "aha" moments -- What is your leadership voice? -- You: winning! -- The journey forward.
Includes bibliographical references.
Keywords: Church work with children